Effects of fluoride and aluminium stress on antioxidant defense, biochemical responses, and soil properties in rice - R. PUSHPALATHA; Dr. P. VIJAYA; Dr. P. Sri Renganathan (ORYZA-An International Journal of Rice, 2026)
Fluoride is naturally present in water, soil, gases, and dust, and elevated concentrations can impose physiological stress on plants. Aluminium (Al³+) toxicity is a major constraint to crop growth, as it disrupts root development, nutrient uptake, and cellular regulatory processes. This study evaluated the effects of varying fluoride ion concentrations (0, 1, 2, 5, 10, 50, and 100 mg L-1), applied alone or in combination with aluminium (Al³+), on rice (Oryza sativa L. cv. Deluxe Ponni). The responses were assessed through changes in the activities of antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and glutathione reductase (GR), which were monitored on a monthly basis. Post-harvest analyses determined carbohydrate and protein contents in rice grains and evaluated soil pH, electrical conductivity, and microbial population. Fluoride-aluminium stress enhanced antioxidant enzyme activities, indicating the activation of defense mechanisms to mitigate oxidative damage. Fluoride alone increased soil pH by reducing acidity, whereas combined fluoride-aluminium treatments resulted in a moderate pH increase, likely due to aluminium hydroxide formation and associated proton dynamics. This slight increase in soil pH promoted microbial activity, and overall, the combined fluoride-aluminium treatment elicited favorable physiological responses in rice and improved soil quality.